2023
DOI: 10.1142/s021797922450111x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of laser dye concentrations in ZnO nanostructures for optimization of random laser emission performance

Abstract: Many nanoforms of zinc oxide (ZnO) structures can be synthesized, such as spheres, rods, flowers, disks and walls, as scatter centers in random laser. However, nanoflower and nanowire shapes in this work have received particular interest due to their wide range of applications, including biological, medical cancer cell detection, gas sensors, and biosensors. In this paper, we investigate the optical and morphological properties of two-shaped nanoparticles as scatter centers in the laser active medium on the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In addition, it has been reported that ZnO nanocrystals, nanofilms, nanowires [46], and bulk structures can be used as nonlinear media to obtain higher-frequency conversion efficiencies from nonlinear effects [47,48]. Also, various ZnO-based nanohybrids have been examined for the enhancement of their nonlinear optical interactions [49][50][51][52][53][54][55][56]. In this work, we highlight the importance of describing a fractional model and optically induced electronic behavior with influence on photoconductivity and electronic mechanisms responsible for Kerr nonlinearity.…”
Section: Nanosecond Twm Studiesmentioning
confidence: 99%
“…In addition, it has been reported that ZnO nanocrystals, nanofilms, nanowires [46], and bulk structures can be used as nonlinear media to obtain higher-frequency conversion efficiencies from nonlinear effects [47,48]. Also, various ZnO-based nanohybrids have been examined for the enhancement of their nonlinear optical interactions [49][50][51][52][53][54][55][56]. In this work, we highlight the importance of describing a fractional model and optically induced electronic behavior with influence on photoconductivity and electronic mechanisms responsible for Kerr nonlinearity.…”
Section: Nanosecond Twm Studiesmentioning
confidence: 99%
“…This integration of optical and microfluidic technologies into biochips underscores their potential for advancing specific and sensitive biosensing applications. [42][43][44] Son, M.H. et al have pioneered the development of optical biochip sensors designed to identify the presence of antibioticresistant bacteria by detecting specific genes associated with antibiotic resistance.…”
Section: Microfluidic Packaging To Engineer Nano-optofluidic Biochips...mentioning
confidence: 99%
“…According to projections, the yearly expenses associated with AMR may escalate to 10 million fatalities and 100 trillion USD by 2050. Therefore, comprehending the evolution and dissemination of AMR is imperative in enhancing the efficacy of antibiotic therapeutic interventions. …”
Section: Emergence Of Optical Biosensors For Antimicrobial Resistance...mentioning
confidence: 99%